Нанопленки металлов в процессах соединения (пайки) керамических материалов - Найдич, Ю.В.; Габ, И.И.; Костюк, Б.Д.; Стецюк, Т.В.; Куркова, Д.И.; Дукаров, С.В. (My University, 2007)
The relief and morphology of metal nanofilms of thicknesses 30 ÷ 100 nm from Ag, Ti, Nb, Cr, Ni which are deposited on Al2O3 ceramics and silicon carbide are investigated on great magnification (up to 2 × 10^6) with the use of atomic force and electron microscopies. The mutual relation of the morphology of films with their wettability by silver and copper is established. The criterion K = WAmet−cer/σmet which determines the process of coagulation and the final structure of metal nanofilms is offered. The influence of the nanofilm covering thickness on the wettability and strength of welded and brazed ceramics joints which reached 260 МPа is investigated.
Keywords: Thin films; morphology; Wetting; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces